Sistem Pakar Untuk Mendeteksi Lakalantas Berbasis Website Menggunakan Metode Forward Chaining - Syahwafaa Andaruni Tribhuwana Tungga Dewi; Risah Subariah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
A traffic accident or traffic accident is an event that causes side effects, namely causing fatalities, claiming lives and only minor injuries. The number of people who experience accidents raises questions regarding the causes and types of accidents experienced. With questions from the community, the author makes an expert system for detecting web-based traffic with the forward chaining method which aims to provide answers to questions and provide direction if you see traffic accidents. The results of this study can provide convenience for the community in consulting with the police and further emphasize the distance between the community and the police to be closer